PENGEMBANGAN PENUNTUN PRAKTIKUM KEANEKARAGAMAN HEWAN BERBASIS CONTEXTUAL TEACHING AND LEARNING MAHASISWA PENDIDIKAN BIOLOGI - Rahmatia Thahir; Nurul Magfirah; Anisa Anisa (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
This development research focused on producing a practicum guide for Biology Education students on Animal Diversity based on Contextual Learning and Teaching. The study used a four-stage process model, which included define, design, develop, and disseminate. The result showed the Animal Diversity practicum guide based on Contextual Teaching and Learning obtained has an average validation value of 91.66% with very valid criteria. It indicated that this product is appropriate for use. The average value of the product was 89.11% which fulfills the practical criteria that mean the student can easily use it. Further research is needed to assess the effective value of the developed product.